Rapid and Visual Identification of Chlorophyllum molybdites With Loop-Mediated Isothermal Amplification Method - Wang, Nan; Zhao, Zhiyong; Gao, Jie; Tian, Enjing; Yu, Wenjie; Li, Hui; Zhang, Juan; Xie, Ruibin; Zhao, Xiaoyan; Chen, Ailiang (Frontiers in Microbiology, 2021)
Chlorophyllum molybdites is a kind of common poisonous mushroom in China that is widely distributed in different areas. Food poisoning caused by accidentally eating C. molybdites has become more frequent in recent years. In 2019, there were 55 food poisoning incidents caused by eating this mushroom in China. Mushroom poisoning continues to be a common health issue of global concern. When mushroom poisoning occurs, an effective, simple, and rapid detection method is required for accurate clinical treatment or forensic analysis. For the first time, we established a loop-mediated isothermal amplification (LAMP) assay for the visual detection of C. molybdites. A set of specific LAMP primers was designed, and the specificity was confirmed against 43 different mushroom species. The LAMP method could detect as low as 1 pg of genomic DNA. Boiled mushrooms and artificial gastric-digested mushroom samples were prepared to test the applicability of the method, and the results showed that as low as 1% C. molybdites in boiled and digested samples could be successfully detected. The LAMP method can also be completed within 45 min, and the reaction results could be directly observed based on a color change under daylight by the naked eye. Therefore, the LAMP assay established in this study provides an accurate, sensitive, rapid, and low-cost method for the detection of C. molybdites.